Exploration of Endophytic Bacteria from Rice Roots as a Biocontrol Agency for Leaf Blight Disease in Vitro - Vina Maulidia; Agustinur Agustinur; Mawaddah Putri Arisma Siregar; Rayhan Amadius Weihan (Universitas Labuhanbatu, 2025)
Background: Endophytic bacteria live within plant tissues without causing disease symptoms and possess strong potential as biocontrol agents through the production of antimicrobial compounds such as bacillomycin, iturin, siderophores, hydrogen cyanide, chitinase, glucanase, protease, and volatile compounds like acetoin, 2,3-butanediol, and H₂S. These metabolites can inhibit leaf blight pathogens, including Xanthomonas oryzae. The prolonged use of chemical pesticides has caused pathogen resistance, environmental harm, and health risks, highlighting the need for eco-friendly biopesticides. Endophytic bacteria provide a sustainable alternative by suppressing pathogens through competition, biofilm formation, and inducing plant resistance. This study aims to explore the potential of endophytic bacteria isolated from rice roots as biocontrol agents against leaf blight pathogens in vitro. Methodology: Endophytic bacteria were isolated from healthy 40 days rice plants in Pajar Village, Darul Hikmah District, Aceh Jaya Regency Aceh Province. Isolation and purification were carried out using the streak plate technique, followed by macroscopic and microscopic characterization. Antagonistic ability was evaluated through the well diffusion method, and the effects of selected isolates on seed vigor and viability were assessed. Findings: A total of 25 isolates were successfully obtained, exhibiting macroscopic and microscopic diversity. Seven isolates inhibited pathogen growth by forming clear zones, with isolate AJY07 showing moderate inhibition (10 mm). These seven isolates (AJY04, AJY06, AJY07, AJY09, AJY11, AJY23, and AJY24) also enhanced seed vigor and viability and reduced infection during germination by 10–20% compared to controls. Contributions: The findings demonstrate the potential of selected endophytic bacteria as environmentally friendly biopesticides to support the development for sustainable rice cultivation